2021
DOI: 10.1177/17470218211057031
|View full text |Cite
|
Sign up to set email alerts
|

The vertical space–time association

Abstract: The space-time interaction suggests a left-to-right directionality in the mind’s representation of elapsing time. However, studies showing a possible vertical time representation are scarce and contradictory. In Experiment 1, 32 participants had to judge the duration (200, 300, 500 or 600 milliseconds) of the target stimulus that appeared at the top, centre, or bottom of the screen, compared to a reference stimulus (400 milliseconds) always appeared in the centre of the screen. In Experiment 2, 32 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 96 publications
(403 reference statements)
5
22
0
Order By: Relevance
“…In a similar way, Ruiz Fernandéz and colleagues (2014) reported that participants were quicker to respond to a square positioned in the upper space when it was paired with a word referring to the future and faster in their response to a square positioned in the lower space when it was paired with a word that referred to the past, suggesting a bottom-to-top time representation. In a similar way, Beracci, Rescott, et al (2021) reported a bottom-to-top representation for temporal durations in the millisecond range, probably according to the more-is-up metaphor. Finally, several studies have reported that the past is mapped at the top and the future is mapped at the bottom (Boroditsky, 2001; He et al, 2018; Topić et al, 2021) in explicit and implicit tasks, suggesting an automatic activation of a temporal concept along a top-to-bottom orientation, reflecting the salience of the experience with falling objects (i.e., the law of gravity).…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…In a similar way, Ruiz Fernandéz and colleagues (2014) reported that participants were quicker to respond to a square positioned in the upper space when it was paired with a word referring to the future and faster in their response to a square positioned in the lower space when it was paired with a word that referred to the past, suggesting a bottom-to-top time representation. In a similar way, Beracci, Rescott, et al (2021) reported a bottom-to-top representation for temporal durations in the millisecond range, probably according to the more-is-up metaphor. Finally, several studies have reported that the past is mapped at the top and the future is mapped at the bottom (Boroditsky, 2001; He et al, 2018; Topić et al, 2021) in explicit and implicit tasks, suggesting an automatic activation of a temporal concept along a top-to-bottom orientation, reflecting the salience of the experience with falling objects (i.e., the law of gravity).…”
mentioning
confidence: 70%
“…Thus, the vertical STEARC effect observed might reflect an association between past and left hand and between future and right hand, suggesting a transposition of the horizontal time representation (Bonato et al, 2012;Bottini & Casasanto, 2013;Fabbri et al, 2012Fabbri et al, , 2013aFabbri et al, , 2013bIshihara et al, 2008;Santiago et al, 2007;Torralbo et al, 2006;Vallesi et al, 2008;Weger & Pratt, 2008) into vertical space. Both spatio-anatomical (hand-based) and extracorporeal (location) hypotheses (see Viarouge et al, 2014 for a review about spatial reference frames involved in the SNARC effect) should be addressed for the vertical STEARC effect (but see Beracci, Rescott, et al, 2021 for preliminary results). In order to rule out this possibility, we performed the same experiment with the instruction that the right hand should be used to press the bottom key while the left hand should press the top key.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations